Total hip arthroplasty, combined with a reinforcement ring and posterior column plating for acetabular fractures in elderly patients: good outcome in 34 patients - Lont, Tõnis; Nieminen, Jyrki; Reito, Aleksi; Pakarinen, Toni-Karri; Pajamäki, Ilari; Eskelinen, Antti; Laitinen, Minna K (Acta Orthopaedica, 2019)
Background and purpose — Low-energy acetabulum fractures are uncommon, and mostly occur in elderly patients. Determining the optimal operative treatment for such fractures is challenging. Here we investigated whether acutely performed total hip arthroplasty plus posterior column plating (THA) reduced complications and reoperations compared with open reduction and internal fixation (ORIF) in elderly patients with acetabular fractures. Patients and methods — We retrospectively reviewed the records of 59 patients, > 55 years of age, with complex acetabular fractures, caused by low-energy trauma, treated between January 2008 and September 2017. Of these patients, 34 underwent acute THA, and 25 ORIF alone. Patient and implant survival were compared between groups using Kaplan–Meier survival analysis and Cox multiple regression. Functional outcomes assessed by Oxford Hip Score (OHS) were compared between the THA patients and those 9 ORIF patients who underwent secondary THA due to posttraumatic hip osteoarthritis (OA) during follow-up. Results — Overall patient survival was 90% (95% CI 82–98) at 12 months, and 64% (CI 47–81) at 5 years. Of 25 ORIF patients, 9 required secondary THA due to posttraumatic OA. Large fragments on the weight-bearing acetabular dome upon imaging predicted ORIF failure and secondary THA. The acute THA group and secondary THA group had similar 12-month OHS. Interpretation — Acute THA including a reinforcement ring resulted in fewer reoperations than ORIF alone in elderly patients with acetabular fractures. These findings support acute THA as first-line treatment for complex acetabular fractures in elderly patients.